Approach to Represent Run-of-River Hydropower Plants in the Short-Term Hydrothermal System Operation Planning - Tiago Norbiato Dos Santos; Andre Luis Marques Marcato; Amanda Pavila Silva (IEEE Access, 2025)
The operation planning of hydrothermal systems is characterized by high complexity due to the inherent temporal and spatial coupling of the problem. To address this complexity, the process is traditionally structured into sequential stages, each focusing on specific aspects according to its time discretization and study horizon. In the context of the Brazilian power system, these stages are referred to as long-, mid-, and short-term planning, with interdependencies formalized through a cost-to-go function. Reservoir storage is one of the main state variables in this function, linking different temporal stages. In long- and mid-term planning, hydropower plants with small reservoirs — typically designed for daily or weekly regulation — are usually modeled as run-of-river units and not considered as state variables, as they do not significantly contribute to interstage coupling. However, in short-term planning, such plants must be explicitly modeled with their corresponding reservoirs to properly account for their ability to respond to load fluctuations. This discrepancy can create challenges when coupling mid- and short-term models, as the cost-to-go function lacks forward-looking information on small reservoirs not represented in the mid-term model. This paper proposes an approach for representing small reservoirs in short-term hydrothermal operation planning. The objective is to capture short-term storage variations while imposing a condition that the final storage level matches the initial level — a necessary criterion for the plant to be treated as run-of-river in the mid-term model. The proposed approach is applied, as a case study, to the Brazilian power system.